Induced mRNA stability in Bacillus subtilis. - Bechhofer, D H (1987)
We have investigated the induced stability of mRNA encoded by the ermC gene in Bacillus subtilis. Induction of ermC gene expression by erythromycin is known to occur at the translational level. We show that this induction is accompanied by an increase in ermC mRNA half-life from about 2 min to about 40 min. Induced stabilization of ermC mRNA occurs independently of induced translation. The regulatory sequences required for stability are promoter-proximal and can confer induced stability on large mRNAs having diverse 3' ends. Translation of the ermC leader peptide and ribosome-stalling in the leader peptide sequence are necessary for induced stabilization.